Dating Methods of Pleistocene Deposits and Their Problems: IV. Amino Acid Racemization Dating - Rutter, N.; Crawford, R.; Hamilton, R. (Geoscience Canada, 1979)
Summary Amino acid racemization dating is used in Pleistocene stratigraphie studies as a tool for correlation and relative age dating of equivalent strata or for the absolute dating of deposits. The method is based upon detection of changes in amino acid isomer distributions that accompany fossilization. The study of amino acids from a geochemical dating perspective began about 25 years ago with the investigations of Abelson (1954) and gathered considerable momentum in the late 1 960s after development of high resolution gas chromatographic (GC) techniques made possiblethe accurate and rapid determination of amino acid isomer distributions. During the last decade, over 200 publications have dealt with various aspects of the method Dating studies have been earner) out with Pleistocene bones, tenth, wood, seeds, coral, foraminifera. clay minerals. marine and fresh-water sediments, and with marine, freshwater and terrestrial molluscs. The method is particularly useful for correlation and relative age dating ot equivalent strata which have experienced similar temperature histories and diagenelic conditions There are two approaches to absolute age dating an uncafibrated and a calibrated method. The uncalibrated method requires a knowledge of the precise temperature history of the fossil. A small error in temperature would lead to a large error in absolute age estimation This severe limitation is ameliorated by application of the calibrated method A number of complications present themselves in amino acid racemization dating Sample contamination is a concern The validity of certain assumptions required for data manipulation may be questioned. The requirement of a knowledge of the precise temperature history of the fossil severely restricts application of the uncalibrated method, particularly m areas such as Canada where wide temperature fluctuations have occurred. Nevertheless, the method has already proven its usefulness and offers so much potential that it cannot be disregarded In Canada. amino acid racemization dating has been applied extensively in the eastern and western Arctic